Plurilingual reading practices in a global context: Circulation of books and linguistic inequalities - Rivière, Marie (Studies in Second Language Learning and Teaching, 2017)
Media consumption is commonly seen as a major way of appropriating languages and cultures. Availability and accessibility of material are essential conditions for developing plurilingual cultural practices. Transnational circulation of cultural goods has reached a particular intensity in today’s world but is still marked by deep language inequalities. Combining sociolinguistic, language education, cultural sociology, and multiliteracy approaches, this study examines how plurilingual readers access books in their different languages. This qualitative analysis is based on 24 in-depth interviews with both migrant and non-migrant adults living in Western Europe. The findings indicate that printed and digital books in dominant languages circulate more easily, and through more visible and formal channels than books in dominated languages. In addition, the local and online book supply in dominant languages is generally cheaper and more varied, thus being more attractive. However, a wider range of means of access to books, and the active participation of the readers themselves in the circulation of cultural goods enable book-reading practices in less disseminated languages. Pedagogical recommendations for language teachers to encourage autonomous cultural practices among learners according to global evolutions and local specificities are provided.